2010
DOI: 10.1016/j.cvdpc.2010.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Low HDL-cholesterol with normal triglyceride levels is the most common lipid pattern in West Africans and African Americans with Metabolic Syndrome: Implications for cardiovascular disease prevention

Abstract: Background Although designed to predict cardiovascular disease and type 2 diabetes mellitus, the Metabolic Syndrome (MetSyn) under-predicts these conditions in African-Americans (AA). Failure of MetSyn in AA is often attributed to their relative absence of hypertriglyceridemia. It is unknown if the African experience with MetSyn will be similar or different to that in AA. Focusing on the lipid profile, our goal was to determine in West Africans (WA) and AA the pattern of variables that leads to the diagnosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
70
4
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 32 publications
17
70
4
4
Order By: Relevance
“…A third of participants had high LDL‐C, high TC, and low HDL‐C, whereas 1 in 10 had high TG levels. Although persons of African descent typically exhibit a favorable lipid profile characterized by high HDL‐C levels,62, 63 it is unlikely that this atheroprotective trait will persist in WAI with the acquisition of other CVD risk factors and increased years of US residence 64. Elevated TG levels were relatively absent in this group, despite the high prevalence of central adiposity; therefore, the traditional definition of metabolic syndrome, which relies on 5 metabolic risk factors—central adiposity, high TG, low HDL‐C, high blood pressure, and high fasting blood glucose—may underestimate the CVD risk of WAI.…”
Section: Discussionmentioning
confidence: 99%
“…A third of participants had high LDL‐C, high TC, and low HDL‐C, whereas 1 in 10 had high TG levels. Although persons of African descent typically exhibit a favorable lipid profile characterized by high HDL‐C levels,62, 63 it is unlikely that this atheroprotective trait will persist in WAI with the acquisition of other CVD risk factors and increased years of US residence 64. Elevated TG levels were relatively absent in this group, despite the high prevalence of central adiposity; therefore, the traditional definition of metabolic syndrome, which relies on 5 metabolic risk factors—central adiposity, high TG, low HDL‐C, high blood pressure, and high fasting blood glucose—may underestimate the CVD risk of WAI.…”
Section: Discussionmentioning
confidence: 99%
“…The low prevalence of hypertriacylglycerolaemia and the rather high prevalence of low HDL-C in our study are noteworthy and consistent with previous studies in Benin (West Africa) (41,42) . An extensive review on the African diaspora in the UK (47) and a recent study including West Africans and African Americans (48) reported a lower propensity of African people to adverse blood lipid profile. However, low HDL-C was rare in the diaspora, which suggests that lifestyle patterns including diet may explain this difference, considering that West Africans are the ancestors of African Americans who have as much as 70 % of their gene pool of West African origin (49) .…”
Section: Discussionmentioning
confidence: 99%
“…Selon Sumner et al (2010), le HDL-C bas représente la dyslipidémie la plus répandue chez les Africains subsahariens. Cette baisse des taux de HDL-C peut être attribuée au mode de vie, l'alimentation et une espérance de vie plus longue (Windler et al, 2007).…”
Section: Discussionunclassified
“…Ce paradoxe est attribué aux différences ethniques entre les niveaux de triglycérides et de HDL-C entre les Afro-Américains et les Caucasiens. Parmi les individus Ouest Africains avec SMet, moins de 25% présentent des concentrations élevées de triglycérides (Sumner, 2010). Sossa et al(2013a) ont rapporté que la prévalence du HDL-C bas était indépendante de l'insulinorésistance.…”
unclassified